A Comprehensive Analysis of Academic Staff Performance of Early Childhood and Elementary Education: The Nexus of Teaching, Research, and Community Service - Akhyar, Yundri; Riyantini, Safiyah; Latif, Mukhtar; Jamrizal, Jamrizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2025)
The effectiveness of lecturers in executing the Tri Dharma of Higher Education teaching, research, and community services a crucial metric for assessing a university's quality, reputation, and competitiveness. Nonetheless, discrepancies in instructor performance across universities, especially Universitas Riau, persist as a considerable concern. This study seeks to determine the extent to which lecturers at Universitas Riau have successfully fulfilled their roles in education, research, and community service. The aim of this research is to delineate and evaluate lecturers' accomplishments according to the criteria of the Tri Dharma of Higher Education. This study utilizes a descriptive quantitative methodology involving 147 permanent lecturers selected through accidental sampling approaches. Data were gathered by documentation and examined employing descriptive statistics, encompassing minimum, maximum, mean, and standard deviation values. The findings indicate that the predominant proportion of lecturers (71.43%) are classified within the